BCPC Congress Harrogate November 2021. (1st December 2021) - Blake, Robin; Matthews, Graham
The 2021 BCPC Congress was held in Harrogate on 2nd and 3rd November and entitled "Providing policy and regulatory support for multi-functional UK agriculture". Julian Westaway (BCPC) opened the congress, welcomed the attendees, described how delighted he was to have this event back in a face to face capacity and thanked the sponsors – Oxford Analytical, Enviresearch, Blue Frog Scientific, Labcorp, TSG, AHDB, BCPC and International Pest Control. Tony Pexton OBE, a Yorkshire farmer and a BCPC Trustee, was the chair of the opening plenary session on the "UK National Action Plan (NAP) for pesticides and new breeding techniques". He introduced the many international challenges facing the agricultural industry including malnourishment and the need to grow more food, climate change and the hopes of COP26, increasing concerns about techniques such as deforestation and materials used in food production, technology such as robotics becoming mainstream, and the implications from Brexit that now allow us to have more independence in setting our own rules.